Effect of Cooling Rate on the Mechanical Properties of Glass Fiber Polypropylene Composites - Kabbani, Mohammed S. (2017)
A Master of Science thesis in Mechanical Engineering by Mohammed S. Kabbani entitled, "Effect of Cooling Rate on the Mechanical Properties of Glass Fiber Polypropylene Composites," submitted in January 2017. Thesis advisor is Dr. Hany El Kadi. Soft and hard copy available.